BPD FUNCTION IMPLEMENTATION UNDER STATUTE 6 YEAR 2016 - Nurdiyana Nurdiyana; Abd. Chaidir Marasabessy Marasabessy; Suanto Suanto; Sulastri Sulastri (Indra Institute Research & Publication, 2022)
The realization of democracy in the village is the birth of the 2014 provision of the village's no.1 law, which is the creation of a village relief agency as a village representative. Becauseya BPD should be able to run the deed as per village law. To achieve the development in the village of guidelines requires synergy between the village government and the BPD. The problem with this research is; 1) how is the implementation of BPD delivery system system of bogor district? , 2) what factors could be called a roadblock to bogor district district in carrying out its function? The study is a fieldwork with a qualitative approach. Data collection is done with interviews and field observations. Primary data sources were obtained from communities of Ciseeng Bogor district of Bogor, BPD members and the village device. Secondary data are obtained from literature and other documents relevant to the study in question. Research - based conclusions suggest that; 1) all BPD members had not fully grasped the pain with the removal, either in controlling the performance of the village head or in absorbing the desires of the local people, and 2) the BPD members had not fully understood the village law command